Zasebnost in nadzor pri uporabi službenih sredstev - Tomšič, Andrej (Delavci in delodajalci, 2023)
The article deals with the issues of workplace privacy and surveillance when using workplace equipment and services. It depicts the conflict of interest between employers, employees and third parties and provides examples of court cases as important guidance for employers in the absence of normative rules in legislation. The existing rules for public administration are shown and recommendations are provided to employers how to adequately address the issues of workplace privacy and surveillance in their internal policies.
Keywords: acceptable use policies; delovna razmerja; delovno pravo; nadzor; personal data protection; privacy; varstvo osebnih podatkov; workplace privacy; workplace surveillance; zasebnost; zasebnost na delovnem mestu